PENEGAKAN HUKUM TERHADAP PEMBATASAN PEMILIKAN DAN PENGUASAAN TANAH PERTANIAN DI KABUPATEN DHARMASRAYA - , Vivi Andrika ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The purpose of this study was to determine the ownership and control of the process of agricultural land in the district exceeds the maximum limit Dharmasraya, for law enforcement to determine the ownership and control of agricultural land in the district exceeds the maximum limit Dharmasraya, and to determine the role of the Land Board and PPAT role in law enforcement the ownership and control of the agricultural land in the district exceeds the maximum limit Dharmasraya. This research is a juridical empirical research that is based on field research as the primary data, and to complement and support the necessary field data literature data as secondary data. Primary data obtained through interviews with informants Head of the Regional Office of West Sumatra Land Consolidation, Regulation and Planning Section Chief and Head of Administration at the District Land Board Land Dharmasraya and 1 (one) person PPAT Dharmasraya practicing in the District. Secondary data obtained through the study of literature. All data obtained from the research literature will be analyzed qualitatively and descriptively elaborated. Based on the results of the study concluded that the enforcement of restrictions on ownership and control of the agricultural land in the district has not run optimally Dharmasraya because legislation is not adequate where the implementing regulations of Law No. 56 Prp/1960 has yet published. Admimistrasi the land registration system has not been well managed so that as such role is not running due to the stagnant BPN is also in conflict with the rules of customary rights held by the community in Dharmasraya.